The peculiarities of eosinophil apoptosis damage in patients with severe therapy-resistant bronchial asthma - L. Yu. Nikitina; F. I. Petrovsky; I. I. Ivanchuk; A. E. Sazonov (Бюллетень сибирской медицины, 2005)
The study aim: to investigate the dynamics of transcription factor p53, proapoptoic (bax, bcl-XS), antiapoptotic (bcl-2, bcl-XL) effectors, IL-5 expression in peripheral blood eosinophils of patients with severe therapy-resistant bronchial asthma (BA). Methods: clinical, functional, allergologic observation, the study of apoptosis effectors expression (Polymerase Chain Reaction). Material: 60 patients with severe BA. Results: low p53 expression and eosinophils apoptosis depression were revealed in therapy-resistant asthmatics. Conclusion: eosinophil apoptosis disregulation – the key mechanism of persistent inflammation of the airways in therapy-resistant BA.